Efektivitas Hukum Penghentian Penuntutan Tindak Pidana Penyalahguna Narkotika Oleh Jaksa Penuntut Umum Melalui Penerapan Restorative Justice (Studi Di Kejaksaan Negeri Minahasa Selatan) - Wurara, Erly Andika; Malik, Faisal; Rumkel, Nam (Dinasti Research, 2025)
The effectiveness of applying restorative justice principles in terminating prosecution for drug abuse offenses is a key effort in creating a more humane criminal justice system. This approach offers an alternative solution through medical and social rehabilitation, particularly for eligible drug addicts, as regulated by Law No. 35 of 2009 on Narcotics and the Attorney General’s Guideline No. 18 of 2021. Using empirical legal research with a qualitative field approach, primary and secondary data were gathered to illustrate how prosecution termination is implemented at the South Minahasa District Attorney’s Office. Findings show that restorative justice aligns with legal provisions and has positive impacts, including offender recovery, reduced prison overcrowding, and improved restorative-based law enforcement. However, implementation still faces challenges. Internally, obstacles include regulatory gaps in the Criminal Procedure Code (KUHAP) and limited understanding or readiness among prosecutors. Externally, differing views among law enforcement and a punitive legal culture also hinder policy effectiveness. Strengthening the substance, structure, and legal culture is essential to optimize restorative justice in drug-related cases.